Political polarization and post 15th general election in Malaysia - Maithilli, Kalaiselvan (2023)
The 15th General Election has been an important ballot in Malaysian political history due to the influence of political polarization. The purpose of this study is to identify the reasons behind political polarization, and it’s impacts on the country’s development. For the purpose of conducting our research, eight informants with different ethnical backgrounds and exposure to various cultures were chosen as our samples. Future leaders will benefit from this research's ability to add to the model of the causes and effects of political polarisation. Using our data analysis and conclusions, we looked into the following two study goals: The factors of political polarization in Malaysia on 15th General Election and the impacts cause by political polarization to the society and the country’s development. The four primary themes that have been identified for all the findings are connected to the political polarisation in the GE-15. All information gathered has declared to add to the corpus of knowledge for further use.